1991
DOI: 10.1262/jrd1977.37.231
|View full text |Cite
|
Sign up to set email alerts
|

Single or Double Inseminations at Fixed-Time Basis on Lambing Rate of Ewes Treated with Porgestogen-Impregnated Intravaginal Sponges during the Non-Breeding Season.

Abstract: Effect of a single or double inseminations at fixed-time basis on lambing rate of ewes treated with 2 different progestogen-impregnated intravaginal sponges during the non-breeding season was investigated in 3 trials (Farms T, H and S). A total of 236 mature Suffolk ewes were treated with either 60 mg medroxyprogesterone acetate (MAP)-or 500 mg progesterone (P) impregnated intravaginal sponge for 9 days and an intramuscular injection of 600 IU PMSG one day before sponge removal. The MAP-and P-treated ewes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
5
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 3 publications
3
5
0
Order By: Relevance
“…Also, there was no significant difference in the ovulation rate and the number of ovulated ewes between the groups with and without ram introduction. These result are in agreement with previous reports [9,14,21] on synchronized estrus and ovulation using p r o g e s t e r o n e o r s y n th e t i c p r o g e s t o g e n impregnated devices in ewes. In Group BR, however, 2 out of 7 ewes showed estrous behavior more than 40 h after sponge removal, and this caused the prolonged mean time (33.0 h) of the estrous onset compared to the other 2 treatments (21-23 h).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Also, there was no significant difference in the ovulation rate and the number of ovulated ewes between the groups with and without ram introduction. These result are in agreement with previous reports [9,14,21] on synchronized estrus and ovulation using p r o g e s t e r o n e o r s y n th e t i c p r o g e s t o g e n impregnated devices in ewes. In Group BR, however, 2 out of 7 ewes showed estrous behavior more than 40 h after sponge removal, and this caused the prolonged mean time (33.0 h) of the estrous onset compared to the other 2 treatments (21-23 h).…”
Section: Discussionsupporting
confidence: 93%
“…E w es w er e r an d o m l y g r o up e d f o r t h r e e treatments with different intravaginal devices inserted for 12 days: Group A) CIDR (type G containing 0.3 g progesterone: InterAg, Hamilton, New Zealand) (Sf=10, SD=4), Group B) Self-made P sponge (containing 0.5 g progesterone) [9,12,14] (Sf=10, SD=4), Group C) intravaginal MAP cream sponge (containing 0.06 g medroxyprogesterone acetate with inunction) (Sf=10, SD=2, D=2). Furthermore, all groups were divided for two additional treatments, with (R) or without ram introduction.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Paulenz et al [19,20] reported that the fertility of ewes inseminated by cervical AI with liquid semen was significantly different among farms, but that the ewe age had no significant effect. In our previous AI study [31] using cervical AI with fresh undiluted semen during the non-breeding season, we also found a farm-related difference in the lambing rates of three farms. In one of the three farms, the mean age of the ewes was higher (5.8 ± 1.7 years old, n=88) and the BCS was lower (2.9 ± 0.5) than the ewes in the other two farms (4.4 ± 1.5 and 3.8 ± 1.4 years old for age, and 3.4 ± 0.6 and 3.3 ± 0.5 for BCS).…”
Section: Discussionsupporting
confidence: 52%
“…However, CIDR-G is not available for sheep production in Japan. To solve this problem, several i n t r a v a g i n a l d e v i c e s i m p r e g n a t e d w i t h progesterone or synthetic progestogen have been examined [7][8][9][10]. Recently, a new method using cream containing 25 mg CAP (chlormadinone acetate progesterone) or 60 mg MAP (intravaginal cream method) has been developed in Japan [11,12].…”
mentioning
confidence: 99%